THE DEVELOPMENT OF STANDARDIZATION NATURAL COLOUR FROM BATIK OF STEAM BARK (Caesalpinia sappan L) BY SPECTROSCOPHY METHOD - Arum Restu Widyasti; Astuti Lestari; Khoirul Amri; Fakhrizal Naufal; Kun Sri Budiasih (Jurnal Penelitian Saintek, 2017)
The purpose of this research is to obtain a method of color standardization which is a consistent assessment of the color formed by secang natural dye, so it can be used as a reference color of natural dyes of batik.Standardization steps of natural dyes included taxonomic examination, preparation of secang dye by extraction, standardization process by spectroscopic measurement, with “rapid” dye as standard, application on batik process including batik pattern making and wax application on batik  and batik coloring process with secang dye. Data was analized by absorbance vs wavelength obtained from red color formed by secang dye. The results showed that the maximum absorption wavelength of the standard red color was obtained at 450.20 nm. This value is used as the standard red color measurement